Analysis of the Implementation of Waqf Wasiar Sharia Insurance Policies in Review from Islamic Law - Azizah Rahmah; Tri Inda Fadhila Rahma (Journal of Indonesian Management, 2022)
This study aims to analyze the implementation of waqf testaments for sharia insurance policies. Based on the Fatwa DSN MUI variation 106/DSN-MUI/X/2016 concerning the Benefits of Waqf Insurance and Funding Benefits in Sharia Life Insurance, it is regulated that the challenge for assets that may be waqf is 45% while in Waqf law it is 1/3 of wealth or Syirkah. This study uses a qualitative technique by using a literature study. The results of this study indicate that the implementation of waqf wills in sharia insurance policies has not been fully implemented and well controlled..